A study on the behaviour of lift core in highrise / Asri Maspade - Maspade, Asri (2006)
At the beginning, the evolution of radically new structural forms gave great stimulus to devising appropriate methods of analysis. In the early days, approximate techniques were being devised for specific; largely two dimensional, structural forms and the analysis of complex three dimensional systems represent a difficult challenge. With regard to horizontal loading, a building is essentially a vertical cantilever. So it can be calculated simplified as traditional method. But the manual method that applied is not accurate approximately for the very complex building. The computer software will assist to produce the faster result. The major part of this study thus concentrates the behaviour the lift core, one type of shear wall under various type of loading act to the building. A lot of outputs produce by the computer, but the main objective is to get the value based on the deflection, stresses and shear force. Real building structure is so complex that even an elaborate computational model will be a considerer able simplification, and the result from the analysis almost is approximate. With the aid of the graphical output result, we will more understand the behaviour and critical position on the lift core. This study also will create the virtual load as the input stage to recognize what happen to the life core if any possible matters like the extreme earthquake.